Fundraising Strategies for Optimizing Zakat Collection in BAZNAS Cirebon - Andhika, Hagi; Setyawan, Edy; Nasir, Abdul (Faculty of Islamic Economics and Business IAIN Syekh Nurjati Cirebon, 2025)
Fundraisingor zakat fund collection is the process of collecting zakat funds issued by muzakki which are then managed by amil zakat bodies or institutions and given to mustahiq zakat. The problem in this study is the lack of understanding of Fundraising strategies as optimization of zakat funds, causing BAZNAS Cirebon City to identify the most efficient and effective method of collecting zakat funds. The purpose of this study is to determine the strategy of Fundraising zakat funds in BAZNAS Cirebon City, explore the implementation of Fundraising zakat funds used in BAZNAS Cirebon City, analysis of Fundraising strategies can optimize zakat fund collection in BAZNAS Cirebon City. This study uses a qualitative approach that is described to obtain data on Fundraising strategies as optimization of zakat fund collection in BAZNAS Cirebon City. The data collection technique in this study uses direct observation of zakat fund collection activities at BAZNAS Cirebon City, interviews with the chief executive, head of the collection division, head of the human resources and general division and collection staff. Data analysis techniques using miles and huberman are data reduction, data presentation and verification. The results of the study in BAZNAS Cirebon City in the strategy of Fundraising zakat funds, Fundraising implementation and optimizing zakat fund collection in BAZNAS Cirebon City. So that the programs can be enjoyed by the people of Cirebon City there is a program from BAZNAS Cirebon City.